BIBLIOMETRIC ANALYSIS OF PUBLICATIONS DISCUSSING THE CONSTRUCTION FEMALES HEROISM WORLDWIDE (1958-2021) - Srikandi, Cut Novita (International Review of Humanities Studies, 2021)
The number of gender studies related to female heroism varies, however to the best of our knowledge, no bibliometric studies have been conducted to examine research trend related to the construction of female heroism in history. Therefore, the aims of this research to investigate the trend of publication related to the female heroism by utilizing bibliometric analysis which become parameter to evaluate and visualize the worldwide publication focus on the development of gender studies. Herein, we identified 753 research articles in English from Scopus database which were published from 1958 – 2021. According to our findings, we highlighted that the most frequently author keywords are gender, feminism, and hero. Besides, the U.S is the ranking first in citation and publication related to the female heroism studies. The U.S is not only become first country with highest number of publication but also the most cited country and the most active country in international collaboration related with the construction of female heroes. The current information on female heroes publication showed that this field is growing rapidly worldwide as well as international research collaboration. In the future research collaboration in this field still needs to improve the construction of gender in society related to the hero construction.